IMPLEMENTASI GREEN ECONOMIC DAN MANAJEMENN BERBASIS SEKOLAH UNTUK MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Adila Listia Fardiani (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2025)
Green Accounting is a branch of accounting science that focuces on estimating and reporting the impact of economic activities on the environment. Green Accounting aims to incorporate environmental elements into traditional financial accounting anjd notification systems, thereby providing a more compherensive view of company performance, not in terms of revenue, but also in terms of environmental sustainability. The benefits of Green Accounting increase sustainable decision making. Information resulting from Green Accounting can help companies make more sustainable bussniness decisions, such as investing in environmentally friendly technology and reducing excessive use of natural resources. Even though Green Accountingbhas many benefits, its implementation still faces challenges, namely that are no clear an globally structrured and regulations for Green Accounting, so the PKM team can use varios different methods and approaches, namely by providing counseling about application of Green Accounting to SMKN 1 CIRUAS. The methods used is by approaching the students and delivering the material as well as discussing it. This PKM activity was carried out on May 30 2024 abd was attended by male/female students majoring in Accounting at SMKN 1 CIRUAS. Despite several challenges, Green Accounting is an important step towards more sustainable accounting. By counting to develop standards continuing to develop standards an regulations, increasing the availability of data and information, and finding cost-effective solutions, Green Accounting can help the PKM team archive sustainable development goals and create a more sustainable future.